Complex Coacervates: From Polyelectrolyte Solutions to Multifunctional Hydrogels for Bioinspired Crystallization - Dominik Gruber; Cristina Ruiz-Agudo; Ashit Rao; Simon Pasler; Helmut Cölfen; Elena V. Sturm (Crystals)
Hydrogels represent multifarious functional materials due to their diverse ranges of applicability and physicochemical properties. The complex coacervation of polyacrylate and calcium ions or polyamines with phosphates has been uncovered to be a fascinating approach to synthesizing of multifunctional physically crosslinked hydrogels. To obtain this wide range of properties, the synthesis pathway is of great importance. For this purpose, we investigated the entire mechanism of calcium/polyacrylate, as well as phosphate/polyamine coacervation, starting from early dynamic ion complexation by the polymers, through the determination of the phase boundary and droplet formation, up to the growth and formation of thermodynamically stable macroscopic coacervate hydrogels. By varying the synthesis procedure, injectable hydrogels, as well as plastic coacervates, are presented, which cover a viscosity range of three orders of magnitude. Furthermore, the high calcium content of the calcium/polyacrylate coacervate (~19 wt.%) enables the usage of those coacervates as an ions reservoir for the formation of amorphous and crystalline calcium-containing salts like calcium carbonates and calcium phosphates. The exceptional properties of the coacervates obtained here, such as thermodynamic stability, viscosity/plasticity, resistance to acids, and adhesive strength, combined with the straightforward synthesis and the character of an ions reservoir, open a promising field of bioinspired composite materials for osteology and dentistry.